2018
DOI: 10.4067/s0717-95022018000200584
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Potential of Polydatin Against Motor Abnormalities and Dopaminergic Neuronal Loss in Rotenone Induced Parkinson Model

Abstract: SUMMARY:Among the neurodegenerative disorders, Parkinson disease (PD) is ranked as second most common. The pathological hallmark is selective degeneration of the dopaminergic neurons in the nigro-striatal regions of brain with appearance of the Lewy bodies. Present study explores the neuro-protective potential of polydatin in terms of amelioration of degeneration of dopaminergic neurons in nigro-striatal regions of brain and distorted neuromotor behavior in the rotenone model of Parkinson's disease. Thirty-six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
3
8
0
Order By: Relevance
“…Currently, we have at our disposal a range of damage‐inducing agents capable of reproducing PD as reliably as possible (de Andrade Teles et al, 2018). The studies included in this review used only neurotoxin‐based models to induce PD, including 6‐hydroxydopamine (6‐OHDA) (Y. Chen et al, 2015), lipopolysaccharide (LPS) (Huang et al, 2018), 1‐methyl‐4‐phenyl‐1,2,3,6‐tetrahydropyridine (MPTP) (Y. Chen et al, 2015; S. Zhang, Wang, Shi, & Feng, 2020), and rotenone (Ahmed et al, 2018; Y. Chen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Currently, we have at our disposal a range of damage‐inducing agents capable of reproducing PD as reliably as possible (de Andrade Teles et al, 2018). The studies included in this review used only neurotoxin‐based models to induce PD, including 6‐hydroxydopamine (6‐OHDA) (Y. Chen et al, 2015), lipopolysaccharide (LPS) (Huang et al, 2018), 1‐methyl‐4‐phenyl‐1,2,3,6‐tetrahydropyridine (MPTP) (Y. Chen et al, 2015; S. Zhang, Wang, Shi, & Feng, 2020), and rotenone (Ahmed et al, 2018; Y. Chen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In general, all of the studies demonstrated the beneficial effects of polydatin at different dosages and administration protocols on the behavioral performance of animals chemically induced to PD. Polydatin prevented motor coordination, muscle performance, and balance dysfunctions, as detected by the rotarod test (Y. Chen et al, 2015), and the occurrence of tremors, bradykinesia, and rigidity, as evaluated by the catalepsy test (Ahmed et al, 2018; Y. Chen et al, 2015). Some studies used an apomorphine‐induced rotational test to detect damage to the dopaminergic system and behavioral dysfunction in PD animals and verified that polydatin was able to decrease rotational movement (Y. Chen et al, 2015; Huang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They also indicated that polydatin improved neuromotor behavior in a rat model of rotenone-induced PD. Thus, the protective effect of polydatin against striatal degeneration is presented in their report [ 68 ]. In a similar report, polydatin meaningfully prevented the rotenone-induced dysregulations of MDA, manganese SOD, glutathione, and thioredoxin in the striatum.…”
Section: Polydatin Against Nddsmentioning
confidence: 99%